Intensive Care Unit Nurses in Iran: Occupational Cognitive Failures and Job Content - Mehri, Fatemeh; Babaei-pouya, Amin; Karimollahi, Mansoureh (Frontiers in Public Health, 2022)
Background: Nurses in critical care units are under a lot of stress because of special conditions caused by the work environment and the high level of knowledge and skills required to work in these units, which can lead to occupational cognitive errors and failures. This study aimed to investigate the relationship between occupational cognitive failures and job content in nurses in the ICU of Ardabil hospitals in 2020. Methods: The present study was a descriptive-analytical cross-sectional study that was conducted in 2020. The study population included nurses working in ICU of hospitals in Ardabil, from which 267 people who were eligible to enter the study were selected. Job cognitive failure and job content questionnaires were used to collect data. Data were analyzed using SPSS software 23. Result: Occupational cognitive failures with work records in the ICU, total work records, and work records in the COVID-19 and non-COVID-19 units are significantly associated. Job cognitive failure was inversely related to the job content sub-scales of skill discretion and decision authority. And directly related to other sub-scales of job content. Conclusions: The results suggest that paying attention to skill discretion, decision authority, psychological job demand, physical exertion, physical isometric loads, job insecurity, supervisor support, and coworker support can reduce occupational cognitive failures, and also consequently improve their productivity.